2006
DOI: 10.1503/cmaj.060464
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity and their association with hypertension and diabetes mellitus in an Indo-Asian population

Abstract: Research D eveloping countries are increasingly vulnerable to the worldwide epidemic of obesity, which affects all segments of the population, including men, women and now children.1,2 Compared with populations in industrialized countries, those in the developing world appear to be at greater risk of the diseases associated with overweight, and cardiovascular disease has become the leading cause of disability and death in many developing countries. 3-5Worldwide, Indo-Asian people are among the populations at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
205
2
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(230 citation statements)
references
References 21 publications
(11 reference statements)
18
205
2
5
Order By: Relevance
“…D iabetes is a chronic disease that affects millions of people and its complications have increasing effects on quality of life and mortality (1,2). The number of people with type 2 diabetes (T2DM) will rise from 135 million in 1995 to 300 million in the year of 2025 (3).…”
Section: Introductionmentioning
confidence: 99%
“…D iabetes is a chronic disease that affects millions of people and its complications have increasing effects on quality of life and mortality (1,2). The number of people with type 2 diabetes (T2DM) will rise from 135 million in 1995 to 300 million in the year of 2025 (3).…”
Section: Introductionmentioning
confidence: 99%
“…The optimal cut-off values for men were lower than those for women regardless of ethnicity for all of the risk factors investigated. This implies that men are at greater risk for CVD than women at a given BMI value (4)(5)(6)12) . Optimal cut-off values for predicting a disease outcome increase with mean BMI when other factors (age, ethnicity, sex, socio-economic status, lifestyle) remain constant.…”
Section: Resultsmentioning
confidence: 99%
“…1 However, BMI cut points for South Asian and Chinese populations have been revised downwards; a BMI of 23.0 -27.4 kg/m² already represents increased cardiovascular risk and that ≥27.5 kg/m² represents high cardiovascular risk. 7 The revision was necessitated by the strong evidence pointing to an increased risk of developing type 2 diabetes, hypertension and dyslipidemia amongst South Asian [8][9][10][11] and Chinese 12 subjects even at BMI levels of <25.0 kg/m², possibly due to a relative excess of adipose tissue or defi cit of lean body mass compared with Europeans for a given BMI. 8,13,14 Studies on Singaporean subjects have demonstrated similar fi ndings; 15,16 in particular, a 70% and 104% increased risk of diabetes was noted for deciles with a mean BMI of only 19.6 and 20.7 kg/m² respectively.…”
Section: Introductionmentioning
confidence: 99%